PENERAPAN PERILAKU KONSUMSI ISLAM PADA PENERIMA BEASISWA SATU KELUARGA SATU SARJANA BADAN AMIL ZAKAT NASIONAL DI JAWA TIMUR (PERSPEKTIF FAHIM KHAN) - Edwin Bahtiar Hidayat; Eko Fajar Cahyono (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This research aims to know how application of Islamic Consumption Behavior Fahim Khan’s Perspektive on Recipients Satu Keluarga Satu Sarjana Badan Amil Zakat Nasional (SKSS BAZNAS) Scholarship in East Java. This method that used is qualitative approach with s case study strategy. Data was collected by interview dan direct observation of the object research. The analysis technique that used is descriptive qualitative analysis that is narrating the result of interview dan direct observation. Based on the result of this study concluded all recipient of Satu Keluarga Satu Sarjana Badan Amil Zakat Nasional (SKSS BAZNAS) scholarship in East Java have been applied Fahim Khan’s perspective of Islamic consumption behavior. Suggestions for further research should apply this research to another scholarship deeply.Keywords: Consumption Behavior, Fahim Khan, world consumption, hereafter consumption